2007
DOI: 10.1037/0735-7028.38.5.523
|View full text |Cite
|
Sign up to set email alerts
|

Increasing severity of psychopathology at counseling centers: A new look.

Abstract: counseling center staff and directors have argued that there has been an increase in severity of psychological concerns among university counseling center clients (R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 17 publications
2
18
2
Order By: Relevance
“…This finding corroborates with earlier studies on university students visiting counselling centers that found younger students with more severe diagnoses than older on psychological distress (Kettmann, Schoen, Moel, Cochran, Greenberg et al, 2007). Our results also suggest that students living in off-campus hostels were 3 times more likely to have psychosocial problems than those living in a campus dormitory.…”
Section: The Correlates Of Psychosocial Problemssupporting
confidence: 83%
“…This finding corroborates with earlier studies on university students visiting counselling centers that found younger students with more severe diagnoses than older on psychological distress (Kettmann, Schoen, Moel, Cochran, Greenberg et al, 2007). Our results also suggest that students living in off-campus hostels were 3 times more likely to have psychosocial problems than those living in a campus dormitory.…”
Section: The Correlates Of Psychosocial Problemssupporting
confidence: 83%
“…Results of this study challenge the literature on counselling centre psychologists' perception that there is a trend of increasing severity of psychopathology in students (Erdur‐Baker et al, ; Gallagher, ; Jenks Kettmann et al, ). This study shows that also in our centre, the severity level remained stable across a 5‐year period.…”
Section: Discussioncontrasting
confidence: 38%
“…Kettmann et al [3] reviewed the perception that student acuity has increased in university counseling centers and identified an increase in the complexity of the students seen in university counseling centers, leading to greater service utilization by a subset of students served by the centers. He concluded that counseling centers need a system in which the complexity of students with multiple diagnoses is acknowledged through the development of a range of therapeutic modalities beyond the traditional individual therapy model.…”
mentioning
confidence: 98%
“…This report highlights the use of a clinical case conference to facilitate the development of multidisciplinary treatment plans designed to diversify services, thereby increasing access for students and improving communication among disciplines in a university mental health clinic. University mental health system studies in the past two decades have documented an increase in severity of presenting complaints at university counseling centers [2,3]. They emphasized a need to shift care toward a "mental health clinic" model [2].…”
mentioning
confidence: 99%